Breed and gender interact to affect the sale price of beef calves sold through video auctions from 2010 through 2014 - McCabe, E. D.; King, M. E.; Fike, Karol; Hill, K. L.; Rogers, G. M.; Odde, Kenneth (My University, 2017)
The objective of this study was to quantify the effect of the potential interaction of breed and gender on the sale price of beef calves marketed through video auctions while adjusting for all other factors that significantly influenced price. Information on descriptive characteristics of lots of beef calves were obtained from a livestock video auction service. Data were available on 20,007 lots of steer calves and 13,804 lots of heifer calves (2106,181 total steer calves and 1239,645 total heifer calves) that sold in 116 video auctions from 2010 through 2014. All lot characteristics that could be accurately quantified or categorized were used to develop a multiple regression model that evaluated the effects of independent factors on the sale price using a backward selection procedure. A value of P < 0.05 was used to maintain a factor in the final model. Breed description of the calves in the lots was 1 of 19 factors included in the original model and was characterized into 6 groups: English, English crosses (EX), English–Continental crosses (ECX), Black Angus sired out of dams with no Brahman influence (AN), Red Angus sired out of dams with no Brahman influence (AR), and Brahman influenced (BR). Breed and gender of the lot interacted (P < 0.0001) to affect the sale price of calves. Lots of AR and AN steer calves had similar sale prices (P = 0.9540; $379.08 and $378.14 per 100 kg BW, respectively) and sold for significantly higher prices than all other steer breed groups. English cross and ECX steer lots had similar sale prices (P = 0.2588; $376.24 and $374.92 per 100 kg BW, respectively) but were greater (P < 0.05) than BR steer calves ($365.61 per 100 kg BW). Among heifer calves, lots of AR heifers sold for the highest price (P < 0.05; $356.02 per 100 kg BW). The AN heifer calves sold for the second highest price at $345.95 per 100 kg BW, and this price was greater (P < 0.05) compared with ECX ($341.50 per 100 kg BW) and EX heifers ($341.14 per 100 kg BW). Brahman-influenced heifer calves sold for the lowest (P < 0.05) price at $334.64 per 100 kg BW compared with heifers of all other breed descriptions. Breed and gender composition of the lots of beef calves interacted to affect the sale price of calves selling through video auctions. The value of the specific breed composition of beef calves is influenced by gender and may be related to buyers purchasing certain breeds of heifer calves as replacements for the breeding herd.
Citation: McCabe, E. D., King, M. E., Fike, K. E., Hill, K. L., Rogers, G. M., & Odde, K. G. (2016). Breed and gender interact to affect the sale price of beef calves sold through video auctions from 2010 through 2014. Journal of Animal Science, 94, 29-29. doi:10.2527/msasas2016-063
Keywords: Beef Calves; Breed; Gender; Agriculture